Reproductive Performance and Expression of Mucin in the Lower Segment of Oviduct Between Indonesian Native Naked-Neck and Normal Feathered Chicken - Ariyadi, Bambang; Sidadolog, Jafendi Hasoloan Purba; Harimurti, Sri; Sudaryati, Sri; Wihandoyo, Wihandoyo; Sasongko, Heru (2016)
Lower segment of oviduct is the primary tissue where microorganisms may invade from external environment colonizing in the vagina. Mucin composed of glycoproteins play significant roles in the barrier against infection on the mucosal surface. The aim of this study was to determine reproductive performance and expression of mucin in the lower segment of oviduct between Indonesian native naked neck and feathered chicken. Six males and 30 females of Indonesia native chicken were paired with a ratio of a male and 5 females Indonesia native naked neck and normal feathered chicken, respectively. Egg production was recorded daily and were hatched every week. The lower segment of oviduct (isthmus, uterus, and vagina) of Indonesian native naked neck and normal feathered chickens were collected. The expression of mucin mRNA in the mucosal oviduct was analyzed by reverse-transcription-polymerase chain reaction (RT-PCR), where as mucin polysaccharides was localized by alcian blue (AB) staining. The result of this research shows that the egg production (20,2%), egg fertility (67,8%), egg hatchability (54,.4%), embryonic morta;ity 13.3%), egg weight (44.5g), and egg index (77.3%) of Indonesian naked neck chicken do not show significant differences compared to that of normal feathered chickens, namely (29.9%), (53.3%), (48.8%), (8.9%), (44.3%), (78.3%), respectively. Mucin mRNA was expressed in the mucosal oviduct of isthmus, uterus, and vagina in both naked neck and normal feathered chickens. These result suggest that the Indonesian native chicken had a lower productivity, higher embryonic mortality and lower hatchability. Moreover, mucin covers the surface of mucosal oviduct in both naked neck and normal feathered chicken probably to form mucosal barrier.